Manejo de conflictos y satisfacción laboral de los trabajadores de la Unidad de Limpieza Pública y Residuos Sólidos de la Municipalidad Distrital de Guadalupe, 2021 - Abanto Rodas, Alexsandra Gissep (2022)
The objective of this research was to determine how conflict management influences the job satisfaction of workers in the public cleaning unit, solid waste of the district municipality of Guadalupe 2021. For this, methods were used: descriptive-inductive, the analytical-synthetic, basic correlation type and non-experimental design; as well as techniques and instruments such as observation, survey, interview and measurement instruments such as the job satisfaction scale; presenting a sample of 77 workers that allowed obtaining the necessary data to analyze the relationship of the variables: Obtaining for the conflict management variable with its dimensions: Loser-loser style, 91.5% of the respondents stated that they do not feel that a conflict is a competition of wills; loser-concessive style 91.5% indicated that they do not feel that conflicts should be avoided and 85.1% in the loser-disregarding style mentioned that conflicts cannot be ignored; and in turn in job satisfaction: the level of material conditions, remunerative benefits, administrative policies, interpersonal relationships, staff development, task performance and authority relationships, it is stated that of the 77 respondents: 31 representing 22% perceive high job dissatisfaction.